Nigeria : Publication of Financial Sector Assessment Program Documentation -- Detailed Assessment of Observance of Insurance Core Principles. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2013)
Nigeria undertook a Financial Sector Assessment Program (FSAP), which included a review of the structure of Nigeria's insurance market and the supervisory framework. The assessment was benchmarked against the Insurance Core Principles (ICPs) issued by the International Association of Insurance Supervisors (IAISs). It is advised that the National Insurance Commission (NAICOM) of Nigeria can expand the objective to include the creation of a fair, safe, and stable insurance sector for the benefit and protection of policyholders.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet